2014
DOI: 10.5213/inj.2014.18.4.187
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Alleviates Ischemia-Induced Memory Impairment by Enhancing Cell Proliferation and Suppressing Neuronal Apoptosis in Hippocampus

Abstract: PurposeNeurogenic lower urinary tract dysfunction (NLUTD) is a possible consequence of several neurological disorders. NLUTD may produce debilitating symptoms and serious complications, such as chronic renal failure, and recurrent urinary tract infections. Many animal studies of NLUTD symptoms have focused on animal models of cerebral ischemia. In the present study, we investigated the effects of treadmill exercise on memory function and its relation to cell proliferation and apoptosis in the hippocampus, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 29 publications
(76 reference statements)
2
34
0
Order By: Relevance
“…Furthermore, according to previous studies, physical exercise improves cognitive function via increased cellular oxygenation [22]. Seo et al [23] indicated that treadmill exercise has protective effects on the hippocampal dentate gyrus granular cells in ischemic gerbils. Nevertheless, the mechanism by which physical exercise induces protection particularly in the CA3 area of the hippocampus following cerebral ischemia remains unclear.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, according to previous studies, physical exercise improves cognitive function via increased cellular oxygenation [22]. Seo et al [23] indicated that treadmill exercise has protective effects on the hippocampal dentate gyrus granular cells in ischemic gerbils. Nevertheless, the mechanism by which physical exercise induces protection particularly in the CA3 area of the hippocampus following cerebral ischemia remains unclear.…”
Section: Introductionmentioning
confidence: 92%
“…The binding of Bcl-2 and Bax could prevent the pore formation on the outer membranes of mitochondria, reduce the release of cytochrome c , inhibit the formation of the apoptosome and thus inhibit activation of caspase family [36]. Previous studies have shown that both passive and pre-ischemic exercise suppressed the apoptosis and reduced neurons loss in the periinfarct area via upregulating expression of Bcl-2 and maintaining the balance ratio of Bax/Bcl-2 [37-39]. Except for Bcl-2 family, caspase-3 is one of the most important downstream executors in the mitochondrial apoptotic pathway, which is considered as an indicator of neuronal apoptosis [40].…”
Section: Discussionmentioning
confidence: 99%
“…Poststroke exercise and EE further augment these processes in various stroke models [36,[55][56][57]. Interestingly, Komitova et al [57] reported that while poststroke EE enhanced neurogenesis in the subventricular zone, unlimited access to exercise beginning 24 h poststroke attenuated this effect.…”
Section: How Do Exercise and Enrichment Enhance Plasticity And Recovery?mentioning
confidence: 99%